Buying Behavior and Farmers’ Practices Regarding Agrochemicals Use on Rice Crop in Punjab - Sharma, Priyanka; Riar, T.S.; Garg, Lavleesh (Indian Journal of Extension Education, 2020)
Use of agrochemicals in India is increasing at the rate of two to five per cent per annum and is about three per cent of total pesticides used in the world. Heavy reliance of agriculture on synthetic chemical fertilizers and pesticides is having critical effects on public health and environment. Consumer buying behaviour is a process of selecting, purchasing and disposing of goods and services according to the needs and wants of the consumers. The study explored the buying behavior of the farmers and practices followed regarding agrochemicals used on rice crop in Punjab. A total of 100 rice farmers were randomly selected from Ludhiana district. Most of the respondents were seeking information from their peer group, nearly 48 per cent were consulting the private dealers for getting the information about agrochemicals whereas 16 per cent of the respondents were going to extension specialists. Most of the rice farmers were purchasing the fertilizers from cooperative societies whereas for purchasing pesticides most of them preferred private dealers. Brand of the product was most important factor considered while purchasing agrochemicals followed by peer group advice, prior experience and product features whereas price of the product was given least importance. The farmers using recommended practices regarding use of agrochemicals were very few in number. Only five percent respondents in rice crop were observing the ETL of various pests before using the control measures. Most of the respondents were cleaning their spray pumps using detergent or soda.
Keywords: Agrochemicals; Buying behaviour; Farmers; Recommended practices; Rice